1981
DOI: 10.1177/1077727x8100900410
|View full text |Cite
|
Sign up to set email alerts
|

Clothing Influence in Adolescent Leadership Roles

Abstract: The interrelationships between four clothing variables (clothing mode awareness, clothing mode conformity, prestige clothing, clothing attractiveness) and three measures of leadership (representational leadership, organizational leadership, composite leadership) were investi gated. The data were collected from a population consisting of the sophomore class of a cen tral Michigan high school containing 119 boys and 109 girls. Correlation coefficients and multiple regression were the major forms of statistical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…The first is a personal judgment (Kaiser, 1989), whether the object has value to you. Of the four types of judgments, judgments of current conditions have received the greatest attention (Davis & Miller, 1983;Golightly, 1976 & Creekmore, 1981;Smucker & Creekmore, 1972;Workman, 1987). The second type of judgment is appropriateness, deciding if the object is correct for this situation (Creekmore, 1974;Evans, 1964;Ferguson, VanRoozendaal & Rule, 1986;Goldman & Goldman, 1981;Hambleton, Roach & Ehle, 1972;Humphrey, Klaasen & Creekmore, 1971).…”
Section: Thought Process Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The first is a personal judgment (Kaiser, 1989), whether the object has value to you. Of the four types of judgments, judgments of current conditions have received the greatest attention (Davis & Miller, 1983;Golightly, 1976 & Creekmore, 1981;Smucker & Creekmore, 1972;Workman, 1987). The second type of judgment is appropriateness, deciding if the object is correct for this situation (Creekmore, 1974;Evans, 1964;Ferguson, VanRoozendaal & Rule, 1986;Goldman & Goldman, 1981;Hambleton, Roach & Ehle, 1972;Humphrey, Klaasen & Creekmore, 1971).…”
Section: Thought Process Theorymentioning
confidence: 99%
“…Lennon and Davis (1988) tested three methods; researcherprovided categories, subject estimates of category usage, and free-response or actual subject category usage. Judgments are usually compared to some norm established by a group (Davis & Miller, 1983;Golightly, 1976;Horridge, Khan & Huffman, 1981;Morganosky & Creekmore, 1981;Smucker & Creekmore, 1972;Workman, 1987). Researchers interested in inference may wish to employ focused interviews or other free-response methods to identify whether subjects seem to be using featurebased or rule-based processing strategies for inferences from clothing.…”
Section: Clothing Studies Relating To Stages Of Thoughtmentioning
confidence: 99%
“…In Europe and European culture, children's dressing culture has exemplified not only the history of fashion (Bigelow, 1970;Mansfield, 1953), but also the textiles and materials available (Evans, 1949;Furches & Staley, 1963;Lee, 1953), the wealth of homes (Rensselaer, 1972(Rensselaer, /1931Workman, 2009), parents' consuming habits (Horridge & Richards, 1984;Stone & Sternweiss, 1994), and the practicality of clothes from a child's point of view (Inomata & Simizu, 1991) as well as the instrumental value of dressing: with dressing, children seek their own place and define themselves in relation to others (Ford & Drake, 1982;Lapitsky & Smith, 1981;Lennon, 1990;Morganosky & Creekmore, 1981;Perry, Schutz, & Rucker, 1983;Seitz, 2003) as adults do (Kwon & Drayton, 2007;McCullough, Miller, & Ford, 1977).…”
Section: Introductionmentioning
confidence: 98%
“…The large body of literature exploring the significance of individual differences in the values and attitudes attached to clothing (e.g., Buckley and Roach, 1974; Kelley, Blouin, Glee, Sweat, and Arledge, 1982; Morganosky and Creekmore, 1981) provides inferential evidence that each perceiver of a clothed model brings something unique to the setting. Rosencranz's (1962) work in developing the Clothing Thematic Apperception Test demonstrated that individual differences among perceivers in the manner in which they react to pictures of clothed models are meaningful and are related to important personal variables such as age, sex, and socioeconomic status.…”
mentioning
confidence: 99%